Physico-Chemical, Thermal and Rheological Properties of Various Fish Protein-Sago Starch Formulas in Keropok Lekor - Mohamed Saeed, Mohamed Abd Elgadir (2010)
This study was conducted to investigate the interaction between fish protein and sago starch using keropok lekor as a model with the following objectives: to study the thermal and physical properties of the model, to optimize the contents used in the model based on their thermal and rheological properties, to study the effects of sodium chloride and sucrose on transition temperatures of gelatinization and to investigate the effect of sodium chloride and sucrose on cooking time of the model. The ingredients used in preparing the formulations were red tilapia (Oreochromis spp.) minced fish, sago starch (Metroxylon sagu), and water in the ranges of 20 - 50, 10 - 40 and 10 - 35, respectively. A two-level factorial design was carried out to obtain the experimental formulations of the model. Differential scanning calorimetry (DSC), texture profile analysis (TPA), sensory evaluation and the changes in thermophysical properties such as thermal conductivity (k), specific heat capacity (Cp), density (ρ), thermal diffusivity (α) and the effects of sodium chloride and sucrose concentrations on the cooking time of the optimized fish protein-sago starch model were conducted. The onset temperatures (To) of the different formulations of the fish protein - sago starch model varied from 60.9 ± 0.5 - 80.8 ± 0.4oC with an average value of 70.9 ± 0.5oC. The formulations had peak temperatures of gelatinization that varied from 65.5 ± 0.1 - 86.0 ± 0.4oC with average value of 75.8 ± 0.3oC. Increasing the ratios of the minced fish in the formulations was found to be the most significant factor affecting the values of To and Tp. The highest hardness value 50.9 N was obtained in the sample formulated with 5: 4: 1 minced fish: sago starch: water, respectively followed by 45.0 N which was obtained in the sample formulated with the ratios of 3.5 minced fish 4 sago starch: 2.25 water. The sensory evaluation study showed that the panelists preferred the model formulated with 2: 1: 1 minced fish: sago starch: water followed by 3.5: 2.5: 2.25 of the components, respectively. The optimum formulation of the model was highly dependant on the ratios of fish protein: sago starch. The addition of NaCl to the optimized formulation resulted in the shifting of the To from 82.2 ± 0.9oC to 98.2 ± 0.1oC, Tp from 94.8 ± 0.2oC to 106.2 ± 0.3oC and Tc from 108.0 ± 0.9oC to 116.3 ± 0.2oC. However, the addition of sucrose shifted To from 82.2 ± 0.9oC to 111.4 ± 0.2oC, Tp from 94.8 ± 0.2oC to 118.2 ± 0.2oC and Tc from 108.0 ± 0.9oC to 119.3 ± 0.3oC. During frying an increase in the thermal conductivity (k), specific heat capacity (cp) and thermal diffusivity (α) values was observed. The k value of the model increased dramatically from 0.418 to 0.584 W/m2.oC in the control. The calculated k values confirmed that the NaCl and sucrose caused an increase in k values of the model from 0.419 to 0.585 W/m2.oC for NaCl and from 0.423 to 0.588 W/m2.oC for sucrose treated ones. The calculated values of thermal diffusivities of the model varied from 1.19 x 10−7 to 1.51 x 10−7 m2 s−1 during deep - fat frying. In summary, it can be concluded that the thermal properties of the model were highly dependant on the ratios of fish protein, sago starch and water used. The optimum formulation was obtained in the model formulated with 2: 1.01: 1 minced fish: sago starch: water, respectively. The shifts in the transition temperatures values of To, Tp and Tc caused by NaCl were 16, 11.4 and 8.3oC, respectively. However, sucrose shifted the transition temperatures values of To, Tp and Tc to 29.2, 23.4 and 11.3oC, respectively. Sucrose was found to be more effective in increasing the onset and conclusion temperature of gelation of the model. The actual cooking time of the control sample of the model was 180 s and the predicted cooking time of the model according to Ansari‟s equation was 195 s. The model with either added sucrose or NaCl needed more time to be cooked